Technology of multilayer and glazed fruit and vegetable chips. - Dudarev, Igor; Panasyuk, Svitlana; Say, Volodymyr; Zahorko, Nadiia; Загорко, Надія Петрівна (Tallinn: Scientific Route OÜ, 2024)
ENG: Fruit and vegetable chips are a growing segment of the global snack market. These chips are an alternative to high-calorie potato chips. Fruit and vegetable chips can be a useful snack between main meals, allowing the human body to get the ne cessary vitamins, macro and micro elements. No oil is used in the production of fruit and vegetable chips, and they do not contain added sugar, artificial colours and flavors. Instead, these chips contain beneficial substances that are rich in fresh fruits and vegetables, albeit in smaller quantities. Because fruits and vegetables lose valuable nutrients during storage, they must be processed into high-quality fruit and vegetable chips. Blanching, immersion in various solutions and osmotic dehydration of the plant raw materials before dry ing are used to reduce the loss of nutrients during the production of fruit and vege table chips and to preserve the taste, smell and colour of the plant raw materials in the finished product. The developed technologies of multilayer and glazed fruit and vegetable chips allow consumers to obtain an innovative product with original taste properties and nutritional composition. The modes of the proposed technology of multilayer chips allow producers to preserve as much as possible the taste and co lour of plant raw materials (fruits and vegetables) in the finished product, as well as nutrients. As a result of combining different types of plant raw materials (vegetables, fruits, seeds) it is possible to obtain a wide range of multilayer chips with different tastes that can satisfy the preferences of different categories of consumers. By com bining plant raw materials, manufacturers can also balance the nutrient content of the chips and obtain a functional product for specific target groups of consumers./////////// UKR: Розроблено технологію виробництва багатошарових і глазурованих фруктово-овочевих чіпсів з підвищеним харчовим складом. Цей спосіб зберігає смак, колір і поживні речовини сировини, а шоколад допомагає збалансувати харчову цінність. Крім того, додавання порошків з ліофілізованих рослин збагачує чіпси вітамінами та мінералами, надаючи їм новий смак і колір.
Технологія багатошарових та глазурованих фруктово-овочевих чіпсів.
Keywords: Fruit chips; vegetable chips; multilayer chips; healthy chips; technology of fruit chips; glazed chips; technology of vegetable chips; properties of chips